Evaluation of the Hepatitis C Testing Strategy for Human Immunodeficiency Virus–Positive Men Who Have Sex With Men at the Sexually Transmitted Infections Outpatient Clinic of Amsterdam, the Netherlands. Issue 9 (September 2020) - Jongen, Vita W.; van Rooijen, Martijn S.; Schim van der Loeff, Maarten F.; Newsum, Astrid M.; de Vos Klootwijk, Louise; Hoornenborg, Elske; Hogewoning, Arjan; van der Valk, Marc; van den Berk, Guido E.L.; Prins, Maria; Heijman, Titia
Abstract : Introduction: As the incidence of hepatitis C virus (HCV) infections remains high among human immunodeficiency virus (HIV)-positive men who have sex with men (MSM) an HCV testing strategy was introduced at the sexually transmitted infections (STI) clinic in Amsterdam in 2017. We aimed to evaluate this HCV testing strategy. Methods: The HIV-positive MSM and transgender women (TGW) were eligible for HCV testing (anti-HCV and HCV ribonucleic acid) at the STI clinic if they did not visit their HIV clinician in the 3 months before the consultation and had not been tested for HCV at the STI clinic in the previous 6 months. All eligible individuals were administered the 6 questions on risk behavior of the HCV-MSM observational study of acute infection with hepatitis C (MOSAIC) risk score; a risk score of 2 or greater made a person eligible for testing. Results: From February 2017 through June 2018, 1015 HIV-positive MSM and TGW were eligible for HCV testing in 1295 consultations. Eleven active HCV infections (HCV ribonucleic acid positive) were newly diagnosed (positivity rate, 0.9%; 95% confidence interval [CI], 0.4–1.5%). Sensitivity and specificity of the HCV-MOSAIC score for newly diagnosed active HCV infections were 80.0% (95% CI, 49.0–94.3%) and 53.7% (95% CI, 50.8–56.5%), respectively. If an HCV-MOSAIC score of 2 or greater were used to determine whom to test, 46.6% of individuals currently tested for HCV would be eligible for testing. Conclusions: Using the new HCV testing strategy, HCV testing was done in 1295 consultations with HIV-positive MSM and TGW in 17 months. We newly diagnosed 11 active HCV infections. The HCV-MOSAIC risk score could reduce the number of tests needed, but some active HCV infections will be missed. Abstract : A new hepatitis C virus (HCV) testing strategy at a sexually transmitted infection clinic identified new active HCV infections. The HCV men who have sex with men observational study of acute infection with HCV risk score reduces the number of tests, although HCV infections will be missed.Supplemental digital content is available in the text.